A study on the mediating effects of job satisfaction on employee loyalty: a case study of a developer company at Johor Baharu / Mutiiah Mohamad - Mohamad, Mutiiah (2017)
Literally, employee loyalty is being described as the ability of the employee or staff members of the organization to stay and contribute well in their jobs for such a long term. In the recent years, resignation of employees did show an increment. The scenario of employees resigning from one company only after a few months of working while then went to seek for another job happened in most companies in Malaysia. This research specifically study on A Developer Company which is one of the constructions developers company in Johor. Hence, since the turnover rates of the employees at the construction sectors are significantly increased based on data shows by the Employment Policy Foundation tabulation and analysis of Bureau of Labor Statistic (2011), there is still a possibility same thing might happen to the developer company. The purpose of this study is to investigate the factors of training, rewards and benefits and working condition as determinants toward employee loyalty instead of how does job satisfaction mediate the relationship between independent variables and dependent variables as the factors that influence the employee loyalty in organizations. Researcher used the stratified sampling method in the research and choose questionnaire as the research instrument that are developed by previous researcher and adopt it into this research. Respondents of this research consist of 155 respondents which are employees of Company X. For overall findings, researcher concludes that employee loyalty in Company X has positive relation between the working condition, rewards and benefits, training and job satisfaction and confirms the partial mediation of Job Satisfaction between the independent variables Rewards/benefits and training with employee loyalty. Lastly, researcher hopes that this research with its findings can help Company X to create new ideas on how to enhance employee loyalty in the company and consider on the recommendation which suggested by the researcher.